(untitled) (Universal International Scientific Journal, 2026)
This article discusses the role of women in raising a healthy generation, statistics on the level of development of women’s sports in our country, the basics of engaging in athletics, and the distribution of training loads in accordance with the physiological period occurring in their bodies.